The marbled crayfish as a paradigm for saltational speciation by autopolyploidy and parthenogenesis in animals - Vogt, Günter; Falckenhayn, Cassandra; Schrimpf, Anne; Schmid, Katharina; Hanna, Katharina; Panteleit, Jörn; Helm, Mark; Schulz, Ralf; Lyko, Frank (Biology open, 2015)
Skip to Next Section - The parthenogenetic all-female marbled crayfish is a novel research model and potent invader of freshwater ecosystems. It is a triploid descendant of the sexually reproducing slough crayfish, Procambarus fallax, but its taxonomic status has remained unsettled. By cross-breeding experiments and parentage analysis we show here that marbled crayfish and P. fallax are reproductively separated. Both crayfish copulate readily, suggesting that the reproductive barrier is set at the cytogenetic rather than the behavioural level. Analysis of complete mitochondrial genomes of marbled crayfish from laboratory lineages and wild populations demonstrates genetic identity and indicates a single origin. Flow cytometric comparison of DNA contents of haemocytes and analysis of nuclear microsatellite loci confirm triploidy and suggest autopolyploidisation as its cause. Global DNA methylation is significantly reduced in marbled crayfish implying the involvement of molecular epigenetic mechanisms in its origination. Morphologically, both crayfish are very similar but growth and fecundity are considerably larger in marbled crayfish, making it a different animal with superior fitness. These data and the high probability of a divergent future evolution of the marbled crayfish and P. fallax clusters suggest that marbled crayfish should be considered as an independent asexual species. Our findings also establish the P. fallax-marbled crayfish pair as a novel paradigm for rare chromosomal speciation by autopolyploidy and parthenogenesis in animals and for saltational evolution in general.
Gesehen am 25.06.2020